Legal Review of the Reform of the Criminal Procedure Law in Indonesia - Tedjo Asmoro; Wieke Dewi Suryandari; Lamijan Lamijan (Referendum : Jurnal Hukum Perdata dan Pidana, 2026)
Reforming Indonesia's criminal procedure law is a crucial step in adapting the justice system to developments in law, human rights, and technology. Law No. 1 of 2023 concerning the Criminal Procedure Code (KUHAP) replaces Law No. 8 of 1981, which has been in effect for more than four decades and will only come into effect in 2026. This reform aims to improve the effectiveness, efficiency, and protection of human rights in the criminal justice process. The changes stipulated in this new law cover various aspects, such as strengthening the rights of suspects and defendants, adjusting investigation and prosecution procedures, and adopting technology in the justice system. With these changes, it is hoped that the Indonesian criminal procedure law will be more responsive to the needs of society and increasingly complex legal challenges. This research employs a normative juridical method, an approach that focuses on the study of legal norms in legislation and relevant legal principles. This approach tries to analyze the content and modifications contained in Law No. 1 of 2023, comparing them with the previous provisions in Law No. 8 of 1981, and examining the normative implications of these reforms in criminal procedural law. Furthermore, this research draws on legal literature, academic journals, and other official documents related to criminal procedural law. This study does not involve interviews or case studies, but rather focuses on normative and conceptual studies of the legal changes that have occurred. Therefore, this research aims to provide a deeper understanding of the reforms in criminal procedural law in Indonesia and their implications for the national criminal justice system.